The Emergence of Internet of Things (IoT): Connecting Anything, Anywhere - Rahman, Md. Arafatur; Asyhari, A. Taufiq (MDPI, 2019)
Internet of Things (IoT) plays the role of an expert’s technical tool by empowering physical resources into smart entities through existing network infrastructures. Its prime focus is to provide smart and seamless services at the user end without any interruption. The IoT paradigm is aimed at formulating a complex information system with the combination of sensor data acquisition, efficient data exchange through networking, machine learning, artificial intelligence, big data, and clouds. Conversely, collecting information and maintaining the confidentiality of an independent entity, and then running together with privacy and security provision in IoT is the main concerning issue. Thus, new challenges of using and advancing existing technologies, such as new applications and using policies, cloud computing, smart vehicular system, protective protocols, analytics tools for IoT-generated data, communication protocols, etc., deserve further investigation. This Special Issue reviews the latest contributions of IoT application frameworks and the advancement of their supporting technology. It is extremely imperative for academic and industrial stakeholders to propagate solutions that can leverage the opportunities and minimize the challenges in terms of using this state-of-the-art technological development.